A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 4 - 14. If your Hospital considers that the proposals in the White Paper offer inadequate safeguards, and agreed the principles and counter proposals advocated in the enclosed draft Memorandum, would your Hospital desire to join with other Voluntary Hospitals in refraining from participation in a National Health Service until adequate safeguards have been secured? The Board of this Hospital would review the position if adequate safeguards were not secured. The above answers represent the considered opinion of the Board of Management of the .....Hospital Signed............... 292/847/2/33